The Effect of Export Concentration on Economic Development in Iraqs - Rahim, Mayada Hassan; Hassan, Qais Mahdi (South Asian Journal of Social Sciences and Humanities, 2025)
The research summarizes how to present and analyze the problem of export concentration in the Iraqi trade balance in terms of quality and quantity, which shows that crude oil accounts for the largest proportion of the structure of commodity exports in Iraq, as is the case with most Arab and non-Arab countries that still depend on oil to finance their annual expenses. It also addresses the most important methods and proposals to address the problem. This comes through following two main policies, one of which is applied in the short term and the second is applied in the long term, and each of them includes sub-policies that are subordinate to it and interconnected with each other. We see that following these two policies is very necessary in order to achieve sustainable and comprehensive economic development in Iraq, which can be applied in all oil countries that depend on extractive raw materials to achieve their imports. When following these two short- and long-term policies, we guarantee getting rid of all the problems of backwardness and lagging behind developed countries, and we can keep pace with global economic development and catch up with progress. The qualitative imbalance in the Iraqi trade balance can be reversed and concentration can be made a good feature essential for developing other economic sectors. Despite our disagreement about the concentration of exports, it results in many risks that cannot be We estimate its effects, whatever they may be, but we deal with it according to a realistic vision that is in line with the variables and to actually achieve a qualitative transition and a real change in the trade balance, in order to achieve economic development.
Keywords: Export concentration; economic development; foreign trade